2001
DOI: 10.1080/152165401317291110
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Versatility of Human Cytochrome P450 Enzymes: The Promise of Blue Roses From Biotechnology

Abstract: SummaryThe cytochrome P450 (P450) enzymes involved in drug metabolism are among the most versatile biological catalysts known. A small number of discrete forms of human P450 are capable of catalyzing the monooxygenatio n of a practically unlimited variety of xenobiotic substrates, with each enzyme showing a more or less wide and overlapping substrate range. This versatility makes P450s ideally suited as starting materials for engineering designer catalysts for industrial applications. In the course of heterolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Formation of II (an analogue of N-FK) is notable, because this compound is the only product that we have identified that has not been reported to result from P450-catalyzed oxidation of indole (29)(30)(31)(37)(38)(39). In contrast, oxidation of indoles (40) -, below detection limit.…”
Section: •−mentioning
confidence: 90%
“…Formation of II (an analogue of N-FK) is notable, because this compound is the only product that we have identified that has not been reported to result from P450-catalyzed oxidation of indole (29)(30)(31)(37)(38)(39). In contrast, oxidation of indoles (40) -, below detection limit.…”
Section: •−mentioning
confidence: 90%
“…They contain the gene of CYP75A from Petunia hybrida, which is responsible for the synthesis of the blue blossom dye delphinidin [142,143]. Comprehensive reviews on P450 in biotechnology including promising future applications and approaches to improve their catalytic properties and performance have been published by Schwanenberg et al [144], Gillam and Guengerich [145], Guengerich [146], Urlacher et al [101], Buchholz et al [147], and Bernhardt [13].…”
Section: Topicmentioning
confidence: 99%
“…Another application of dye production by CYP involves horticulture. For example, the production of flowers with unusual colors, e.g., blue roses, is performed by transferring CYP coloration genes from other plants [39]. Accordingly, the introduction of CYP, which oxidizes indole into a variety of colored compounds, into flowering plants, is an alternative method that is proposed in the horticultural industry.…”
Section: Applications Of Cytochrome P450 Biocatalystsmentioning
confidence: 99%